Pengaruh Moving Average dan Transaction Volume pada Return Saham Perbankan Indonesia - Majiah, Valdi Sayoga; Kelana, Said (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
This study investigates the impact of Moving Average (MA) Stock prices and Transaction Volume on Stock returns in the Indonesian banking sector, specifically focusing on the LQ45 index from 2020 to 2023. It delves into the concepts of Efficient Market Hypothesis (EMH), Behavioral Finance, and Technical Analysis. EMH posits that Stock prices reflect all available information and are hard to consistently beat, while Behavioral Finance suggests that psychological factors can lead to market inefficiencies exploitable by technical analysis. Employing a quantitative approach and data from the Indonesia Stock Exchange (BEI), the study finds that MA and Transaction Volume positively and significantly influence Stock returns in the banking sector. However, variations exist in individual bank samples due to factors like fundamentals and unique behaviors, which cannot be solely determined from historical Stock prices. Thus, the research underscores the importance of considering additional factors beyond past price trends when analyzing the Stock performance of individual banks.